2017
DOI: 10.1002/app.44803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graphene oxide and chemically reduced graphene oxide on the curing kinetics of epoxy amine composites

Abstract: The curing kinetics of epoxy nanocomposites prepared by incorporating graphene oxide (GO) and chemically reduced graphene oxide (rGO) have been studied using isothermal and nonisothermal differential scanning calorimetry. The kinetic parameters of the curing processes in these systems have been determined by a Kamal and Sourour phenomenological model expanded by a diffusion factor. The predicted curves determined using the kinetic parameters fit well with the isothermal DSC thermograms revealing the proposed k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…By increasing the filler content to 0.8 wt %, the broad peak continues to shift to the left with a peak temperature at 259 °C. This indicates that imidazole modified GO can indeed play the role in catalyzing epoxy resin-anhydride curing system, and the increase in the content of IMD-Si@GO results in a higher reaction rate [ 36 , 37 ]. Additionally it is obvious that a small peak appears at around 191 °C by adding IMD-Si@GO nanosheets, without movement when the filler content rises.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the filler content to 0.8 wt %, the broad peak continues to shift to the left with a peak temperature at 259 °C. This indicates that imidazole modified GO can indeed play the role in catalyzing epoxy resin-anhydride curing system, and the increase in the content of IMD-Si@GO results in a higher reaction rate [ 36 , 37 ]. Additionally it is obvious that a small peak appears at around 191 °C by adding IMD-Si@GO nanosheets, without movement when the filler content rises.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the curing behavior of epoxy systems is essential because the thermal and mechanical properties of the epoxy composites depend on the formation of the crosslinked molecular network in the system and the structure of the interphase region between the continuous phase (resin) and on the discontinuous phase (reinforcement). In a previous research, the curing kinetics of epoxy nanocomposites prepared by incorporating graphene oxide and reduced graphene oxide (rGO) have been studied using isothermal and non-isothermal differential scanning calorimetry [ 34 ]. The GO load in epoxy amine systems resulted in a decrease of peak exotherm temperature and a reduction in the curing times, indicating a significant enhancement of curing reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The results are consistent with a study by Yousefi et al [56], where an increase in T g was observed for GO filler loadings of 0.5-2 wt.% in an epoxy matrix. Improvements in the T g value have been attributed to higher cross-link density due to reactions between the oxygen containing functional groups on GO and the epoxy matrix [66]. This suggests that the addition of small amounts (<0.6 wt.%) of GO to the bio-epoxy did not interfere with polymer chain mobility upon curing which resulted in greater cross-linking density with a decrease in the polymer chain mobility.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%